Analisis Kesulitan Belajar dan Miskonsepsi Mahasiswa dalam Praktikum Berbasis Proyek - Muhammad Nasir (IAIN Palangka Raya, 2017)
Abstract: The aim of this study is to analyze the difficulty of learning and student collage misconception on experiment base project. Research approach used is qualitative descriptive. Student college misconception is tested by Certainty of Response Index (CRI). The subject of this research is physics education student collage of Palangka Raya Islamic state institute. Result of this research show that difficulty of learning student collage are 9% on determining the topic, 9% on identification of device and matter, 22% on arranging the procedure, 35% on arranging the schedule of project, 39% on collecting the data, 4% on displaying the data, 87% on choosing the data analysis technique, 13% on discussing the result of data analysis, and 4% on concluding the result of data analysis. Misconception of student collage on data analysis technique is 74,64% and not understanding the concept is 3,92%. Result of this research is concluded that the highest of learning difficulty of student collage on choosing the data analysis technique. This case is caused by misconception and not understanding of student collage on data analysis technique. Suggestion of this research is comprehension of student collage on concept of data analysis technique be needed before implementing experiment base project.